Pengaruh Metode Latihan Resistance Band dan Ladder Drill Terhadap Kecepatan Tendangan Sabit - Abdul Aziz, Lukman; Riski Adi Wijaya, M; Mega Widya Putri; Nuari Panggraita, Gilang (Jurnal Muara Olahraga, 2025)
This study aims to analyze the effect of resistance band and ladder drill training methods on crescent kick speed among pencak silat athletes from IPSI Kota Pekalongan. The research employed a quantitative experimental approach using a pretest-posttest control group design. Sixteen athletes were selected and divided into two groups through ordinal pairing: one group trained with resistance bands, while the other used ladder drills. The instrument used was a 10-second crescent kick speed test. The paired sample t-test results showed significant improvements in both groups (p < 0.05). An independent sample t-test revealed a significant difference between the groups, with the resistance band method proving more effective in increasing crescent kick speed. The study concludes that both training methods positively impact crescent kick speed, but resistance band training is statistically more effective.